A novel non‐invasive identification of genome editing mutants from insect exuviae. (16th April 2021) - Wang, Xiao‐Xiao; Li, Jing; Wang, Tong‐Xin; Yang, Yi‐Nuo; Zhang, Hai‐Kang; Zhou, Meng; Kang, Le; Wei, Li‐Ya
Abstract: With the wide application of genome editing in insects, a simple and efficient identification method is urgently needed to meet the increasing demand for mutation detection. Here, taking migratory locusts as a model system, we developed a non‐invasive method to accurately identify genome‐edited mutants by using DNA from insect exuviae. We compared the quantity and quality of genomic DNA from exuviae in five instar hoppers and found that the 1st instar exuviae had the highest DNA yield and content, while the 3rd instar exuviae had the best quality. Consensus genotypes were identified from genomic DNA of hoppers at different developmental stages in the same individuals. Moreover, we demonstrated that the amplification products from DNA extracted from locust exuviae are the consensus sequences with those from the hemolymph and foreleg pre‐tarsus. Therefore, non‐invasive samples provide the same genotyping results as minimally invasive and invasive samples of the same individuals. Furthermore, this identification method that uses genomic DNA from exuviae can be used for early screening of positive genome‐edited individuals in each generation for adult crossing. In our study, the non‐invasive identification method was not only simpler and provided results earlier than existing methods, but also had a better reproducibility and accuracy. This non‐invasive identification approach using genomic DNA from exuviae can be adapted to meet the growing demand for genetic analysis and will find wide application in insect genome editing research. Abstract : In this study, we developed a novel, simple, non‐invasive, reproducible and accurate method to identify genome‐edited mutants by using DNA from insect exuviae. Taking migratory locusts as a model, we can early screen the positive genomic edited individuals in each generation by the novel non‐invasive method. This non‐invasive identification method can be widely applied to precisely screen genetically modified mutants generated by genomic editing technology. In addition, most insect species produce exuviae during the growth, so exuviae can be easily collected. Our method has great potential and universality for application in other insects and animals.